Changing Europe's Budgetary Framework: Implications for the German Independent Advisory Board - Christian Bender; Fabio Botta; Thomas Lenk (Intereconomics, 2023)
European governance is in a state of upheaval. Due to the impact of the coronaviruspandemic, the Russian war of aggression in Ukraine and the energy price crisis, Europeanfiscal policy has come under increasing pressure. In this complex situation, the EuropeanCommission considers a return to the previous fiscal rules to be impracticable and haspresented reform proposals. These include the strengthening of national independent fiscalinstitutions through the bundling and expansion of tasks and duties. This article examinesthe implications that the implementation would have with regard to the Independent AdvisoryBoard to the Stability Council in Germany.
Keywords: H63; H77; H83; 330